BA 226 - Business Law and the Legal Environment - Saylor Academy; Keith Tierney; Andy Schmidt (2018)
Keith Tierney updated and enhanced this work in 2018 based on an adaptation of Business Law and the Legal Environment by the Saylor Academy.